Frequency and predictive factors of minimal hepatic encephalopathy before and after sustained virological response in HCV cirrhosis - Piedade, Juliana (2022)
Ministry of Health. Bonsucesso Federal Hospital. Gastroenterology and Hepatology Unit. Rio de Janeiro, RJ, Brazil.